2023
DOI: 10.3390/pr11020309
|View full text |Cite
|
Sign up to set email alerts
|

NADES-Based Cork Extractives as Green Ingredients for Cosmetics and Textiles

Abstract: The demand for products based on natural ingredients is increasing among cosmetic and textile consumers. Cork extracts contain components of interest with special properties, including antioxidant, anti-inflammatory, and antibacterial activities, that might improve the effectiveness of cosmetic formulations currently on the market and may impart new characteristics to textiles. The main goal of this work was to investigate the effect of the incorporation of three cork extracts into two commercial cosmetic form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The total phenolic content was determined using the Folin−Ciocalteu reagent with some adaptations. 27 An amount of 2 μL of catechol (≈ 1 mg/mL) or instant coffee (≈ 50 mg/mL) dissolved in DMSO was added to 10 μL of Folin−Ciocalteu reagent, followed by the addition of 120 μL of distilled water and stirring. After 1 min, 40 μL of 15% Na 2 CO 3 (sodium carbonate) and 28 μL of distilled water were added, and the absorbance was read after 2 h at 750 nm and compared to a blank with distilled water using a microplate reader (BioTek, SYNERGY H1M2).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total phenolic content was determined using the Folin−Ciocalteu reagent with some adaptations. 27 An amount of 2 μL of catechol (≈ 1 mg/mL) or instant coffee (≈ 50 mg/mL) dissolved in DMSO was added to 10 μL of Folin−Ciocalteu reagent, followed by the addition of 120 μL of distilled water and stirring. After 1 min, 40 μL of 15% Na 2 CO 3 (sodium carbonate) and 28 μL of distilled water were added, and the absorbance was read after 2 h at 750 nm and compared to a blank with distilled water using a microplate reader (BioTek, SYNERGY H1M2).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The total phenolic content was determined using the Folin–Ciocalteu reagent with some adaptations . An amount of 2 μL of catechol (≈ 1 mg/mL) or instant coffee (≈ 50 mg/mL) dissolved in DMSO was added to 10 μL of Folin–Ciocalteu reagent, followed by the addition of 120 μL of distilled water and stirring.…”
Section: Methodsmentioning
confidence: 99%
“…In certain food-related studies, emulsification in the presence of a NaDES in the aqueous phase has been reported without a temperature increase, achieved by using an ultra-turrax ® homogenizer at high speed for several minutes, a process known to elevate the sample temperature due to friction [38,48]. On the other hand, Rocha et al and Barros Santos et al added a NaDES at room temperature but after the emulsification process [41,42]. Here, the full antioxidant spectrum BGCE was introduced in an O/W cream using the DAC process as the formulation process according to Section 2.6.…”
Section: Cream Preparationmentioning
confidence: 99%
“…A recent study by Jamaleddine et al demonstrated that the inclusion of a Proline/Glycerol NaDES-based tomato extract in a moisturizing cream was feasible, but the impact of the NaDES on the properties or the stability of the product was not described [40]. More recently, Rocha et al enriched two commercially available creams with NaDES-based extracts, noting diverse effects on the characteristics and stability of the final mixture [41]. It is noteworthy that, in this specific case, the NaDES-based extract was not part of the manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…Rocha et al [90] emphasized the effectiveness of NaDES-based extracts from botanical matrices as cosmetic ingredients. By the heating and stirring technique, the research team prepared three eutectic solvents composed as follows: lactic acid-glycerol 1:1 and 10% water (NADES 1), lactic acid-glycine 5:1 and 13% water (NADES 2), and lactic acid-sodium citrate 4:1 and 31% water (NADES 3).…”
Section: Nades In the Cosmetic Fieldmentioning
confidence: 99%